2011
DOI: 10.1371/journal.pone.0028398
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Foundations of Reproductive Lethality in Arabidopsis thaliana

Abstract: The SeedGenes database (www.seedgenes.org) contains information on more than 400 genes required for embryo development in Arabidopsis. Many of these EMBRYO-DEFECTIVE (EMB) genes encode proteins with an essential function required throughout the life cycle. This raises a fundamental question. Why does elimination of an essential gene in Arabidopsis often result in embryo lethality rather than gametophyte lethality? In other words, how do mutant (emb) gametophytes survive and participate in fertilization when an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(99 citation statements)
references
References 82 publications
5
94
0
Order By: Relevance
“…For protein function classification, we utilized a system (Supplemental Table S3) developed for past work on mutant phenotypes in Arabidopsis (Meinke et al, 2003;Bryant et al, 2011;Muralla et al, 2011). To streamline this effort and facilitate comparisons of greatest interest, we limited function assignments to unique genes, essential seed and gametophyte genes, and proteins localized to chloroplasts and mitochondria.…”
Section: Protein Function and Mutant Phenotypesmentioning
confidence: 99%
See 3 more Smart Citations
“…For protein function classification, we utilized a system (Supplemental Table S3) developed for past work on mutant phenotypes in Arabidopsis (Meinke et al, 2003;Bryant et al, 2011;Muralla et al, 2011). To streamline this effort and facilitate comparisons of greatest interest, we limited function assignments to unique genes, essential seed and gametophyte genes, and proteins localized to chloroplasts and mitochondria.…”
Section: Protein Function and Mutant Phenotypesmentioning
confidence: 99%
“…A recent comparison of functions associated with defects in embryo and gametophyte development revealed that although interfering with DNA replication and RNA modification typically disrupts embryo rather than gametophyte development, and blocking cytosolic translation often leads to gametophyte defects, extensive overlap exists between protein functions required for embryo and gametophyte development (Muralla et al, 2011). Therefore, one cannot explain the difference between embryo and gametophyte mutants on the basis of protein function alone.…”
Section: Protein Function and Mutant Phenotypesmentioning
confidence: 99%
See 2 more Smart Citations
“…Meiotic drift, as indicated by reduced transmission frequencies of the tup5-2 and tup5-3 insertion alleles in reciprocal crosses with the wild type, is likely due to a dysfunction of ovules and pollen grains carrying this genotype. The reduced fitness of gametes carrying a TUP5 null allele indicates that they are not exclusively cross-fed from surrounding tissues but need a certain degree of Arg autotrophy (Muralla et al, 2011). However, survival of some gametes also shows that maternal tissue ensures at least limited Arg supply to ovules and pollen grains.…”
Section: Tup5 Is Required For Gametogenesis and Seed Developmentmentioning
confidence: 99%